Political and economic forces in Colombian society as reflected in the literature of "La Violencia" (Forças políticas e econômicas na sociedade colombiana como refletido na literatura da violência) - Geithman, David T.; Landers, Clifford E. (Ciência & Trópico, 2011)
RESUMO Através da literatura de ficção, estuda o impacto da violência de massa na sociedade colombiana após a 2ª Guerra Mundial. Relaciona as principais obras de ficção que tratam do tema. Analisa, como amostra, os romances El Cristo de Espaldas, de Eduardo Caballero Calderón; La mala hora, de Gabriel Garcia Márquez; e Uisheda, de Alvaro Valencia Tovar. Defende a utilidade da literatura de ficção e assinala algumas de suas limitações para a ciência social.ABSTRACTPolitical and economic forces in colombian society as reflected in the literature of ‘la violencia’. v. 20, n. 2, p. 317-336, jul./dez. 1992.Throug the fictional literature, studies the impact of mass violence in Colombian society after World War II. Enrolls the main novels that treat the theme. Analyzes, as a sample, three novels: Eduardo Caballero Calderón' s El Cristo de espaldas, Gabriel Garcia Marquez's La mala hora, and Alvaro Valencia Tovar's Uisheda. Argues for the usefulness of fictional literature and stresses some of its restraints to social sciences.RÉSUMÉLes forces politiques et économiques dans la société colombienne comme un reflet dans la littérature de ‘la violence’. v. 20, n. 2, p. 317-336, jul./dez. 1992.A partir de la littérature de fiction, l’auteur étudie les répercussions de la violence de masse dans la société colombienne après la II ème Guerre Mondiale. Il montre les principales oeuvres de fiction qui se rapportent à ce sujet et analyse les romans El Cristo de Espaldas, de Eduardo Caballero Calderón; La mala hora, de Gabriel Garcia Márquez e Uisheda, de Alvaro Valencia Tovar. Il défend également l’utilité de la littérature de fiction et souligne quelques-unes de ses limitations pour la science sociale.